Social Media Influencer as Marketing Communication of “FORTIVIT” Rice from Perum BULOG - Teradijah Febriani; Andre N Rahmanto; Albert Muhammad Isrun Naini (International Journal of Science and Applied Science: Conference Series, 2022)
In the era of globalization, digital technology continues to develop.  It can be seen by the increasing number of internet and social media users. The development of digital technology also causes changes in consumer behavior, thus requiring companies to be more adaptive to changes and establish their communication strategies. The development of social media as a digital communication tool continues to grow and becomes one of the opportunities as well as challenges for companies to improve their performance. The selection of the right digital media needs special attention, one of which is a digital influencer or Social Media Influencer (SMI). The role of Social Media Influencers (SMI) is increasingly important to shape consumer attitudes and corporate image.  This study uses qualitative methods through observation and interviews with informants who meet certain requirements. Perum BULOG, one of the State-Owned Enterprises (BUMN) which is an important sector in the food industry, is the focus of the study.  The results of the study indicate that Perum BULOG's marketing communication strategy in selecting Social Media Influencers is based on the credibility of influencers who influence the delivery of messages.